Management Styles of Chiefs of Police in Northern Samar - Loreto, Joy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the management styles of Chiefs of Police in the municipalities of Northern Samar and their contribution to peace and order using Luther Gulick's POSDCORB framework. Specifically, it described the respondents' demographic and professional profiles, assessed the management styles of Chiefs of Police across the functions of planning, organizing, staffing, directing, coordinating, reporting, and budgeting, and identified organizational factors affecting police administration. The study employed a quantitative descriptive-correlational research design involving 292 respondents, consisting of Chiefs of Police, Police Non-Commissioned Officers, Non-Uniformed Personnel, and Municipal Advisory Group for Police Transformation and Development members. Data were collected using researcher-made questionnaires validated by experts and tested for reliability through Cronbach's alpha, and were analyzed using descriptive and inferential statistical techniques. The findings revealed that the respondents were predominantly male, married, college graduates with considerable law enforcement experience, professional training, and organizational affiliations. The Chiefs of Police demonstrated effective management practices across all POSDCORB functions, with directing and reporting receiving the highest assessments, while planning, organizing, staffing, coordinating, and budgeting were regularly practiced. Despite these strengths, police organizations continued to experience challenges related to staffing shortages, limited financial and logistical resources, and inadequate support for community-based auxiliary forces. The study further found that professional characteristics, particularly educational background, years of service, rank progression, training and certifications, and professional affiliations, played a greater role than personal demographic characteristics in influencing management styles. The study concludes that strengthening leadership development, professional education, resource support, and management competencies may further enhance organizational effectiveness and peace and order initiatives in Northern Samar. This study supports Sustainable Development Goal (SDG) 16: Peace, Justice and Strong Institutions by promoting effective and accountable police leadership and SDG 11: Sustainable Cities and Communities through strengthened local peace and order. Its findings contribute to institutional, governance, and community sustainability by providing evidence that can support leadership development, organizational improvement, and public safety initiatives.
Keywords: Budgeting; Chiefs of Police; Management Styles; Northern Samar; Peace and Order; POSDCORB; Public Administration